Scattering of oblique waves by permeable vertical flexible membrane wave barriers. (January 2017) - Koley, S.; Sahoo, T.
Abstract : Highlights: Scattering of oblique gravity waves by vertical flexible porous membranes is studied. Analytic solution of the BVPs is obtained using eigenfunction expansion method. Numerical solution of the BVPs is obtained using coupled boundary element-finite difference method. Effectiveness of the vertical membranes as wave barriers is analyzed. Abstract: The interaction of obliquely incident surface gravity waves with a vertical flexible permeable submerged membrane wave barrier is investigated in the context of three-dimensional linear water wave theory. From the general formulation of the submerged membrane barrier, the performance of bottom-standing, surface-piercing and fully extended membrane wave barriers are analyzed for various values of wave and structural parameters. The analytic solution of the physical problem is obtained using eigenfunction expansion method and a coupled boundary element-finite difference method has been used to get the numerical solution. In the boundary element method, since the boundary condition on the membrane barrier is not known a priori, the membrane response and velocity potentials are solved simultaneously using appropriate discretization with the help of finite difference scheme. The convergence of the analytic and numerical solution techniques is discussed. The study reveals that for suitable combination of wave and structural parameters, approximately (45–50)% incident wave energy can be dissipated irrespective of membrane barrier configurations. Further, in certain situations, nearly full wave reflection and zero transmission occur for all barrier configurations. The study will be useful in the design of flexible permeable membrane to act as an effective wave barrier for creation of tranquility zone in the marine environment.